PERBANDINGAN KEMAMPUAN ADAPTASI BAKTERI Staphylococcus aureus dan BAKTERI Escherichia coli PADA EKSTRAK DAUN KARAMUNTING (Melastoma malabathrium) - Hujjatusnaini, Noor; Amin, Astuti Muh; Febrianty, Riafany; Maisyarah, Annisa; Agriana, Brenda Mila; Septianingrum, Dwi Dian; Maradona, Maradona; Wulandari, Noor Sari (INSTITUT AGAMA ISLAM NEGERI AMBON, 2022)
Karamunting plant (Melastoma malabathricum) contains ethonol which is able to inhibit the growth of gram-negative bacteria such as Escherichia coli, S. aureus, S. sonnei, C. jejuni, E. colaceae and P. aeruginosa. This study is an experimental study that aims to compare the adaptability of Staphylococcus aureus and Escherichia coli bacteria by providing concentrations of karamunting leaf extract 20% 40%, 60%, and 80% within 24 hours, 48 hours and 72 hours. The results showed that the positive and negative control treatments were not able to inhibit the growth of Escherichia coli and bacteria Staphlococcus aureus. Karamunting leaf extract (Malastoma malabathrium) has similarities that are effective in inhibiting the bacteria Staphylococcus aureus and Escherichia coli bacteria with a concentration of 60%. In addition, there are differences in adaptability between Staphylococcus aureus and Escherichia coli bacteria. bacteria are Staphylococcus aureus more adaptable than Escherichia coli bacteria, because they produce a smaller inhibition zone than Escherichia coli bacteria. Keywords: Karamunting, Escherichia coli, Staphlococus aureus, Adaptation